Association of acrylamide exposure with markers of systemic inflammation and serum alpha-klotho concentrations in middle-late adulthood - Gan, Lin; Wang, Jiaoyang; Qu, Kang; Jiang, Wei; Lei, Yuhong; Dong, Ming (Frontiers in Public Health, 2025)
BackgroundAcrylamide (AA) is a ubiquitous environmental contaminant linked to systemic inflammation and oxidative stress in animal studies; however, the epidemiological evidence is still lacking. This study aimed to evaluate the association of AA exposure with markers of systemic inflammation and serum concentrations of an anti-aging protein, α-klotho.MethodsThe study used data of 1,545 adults aged 40–79 years from the National Health and Nutrition Examination Survey (NHANES) 2013–2016. Internal AA exposure was assessed using hemoglobin adducts of acrylamide and glycidamide (HbAA and HbGA, respectively), the sum of HbAA and HbGA (HbAA + HbGA), and the ratio of HbGA and HbAA (HbGA/HbAA). Two novel indicators, systemic immune-inflammation index (SII) and system inflammation response index (SIRI), were calculated using the lymphocyte, platelet, neutrophil, and monocyte counts. The serum concentration of soluble α-klotho was measured using enzyme-linked immunosorbent assay. Multivariable linear regression models were used to estimate the associations of AA hemoglobin biomarkers with systemic inflammation indicators and serum concentration of α-klotho.ResultsEach one-unit increase in ln-transformed HbAA, HbGA, and HbAA+HbGA was associated with an increase in SII in models adjusted for age, sex, and race/ethnicity [regression coefficient (β) = 32.16, 95% confidence interval (CI): 3.59, 60.73; β =36.37, 95% CI: 5.59, 67.15; and β = 37.17, 95% CI: 6.79, 67.55, respectively]. However, the associations were no longer significant after additional adjustment for lifestyle factors. Higher HbAA and HbAA+HbGA predicted lower serum α-klotho concentrations (β = −35.76 pg./mL, 95% CI: −63.27, −8.25; β = −33.82 pg./mL, 95% CI: −62.68, −4.96, respectively).ConclusionThe hemoglobin adducts of AA parameters, as biomarkers of internal AA exposure, were associated with reduced serum concentrations of α-klotho among the United States population in their middle-late adulthood. The findings indicated that exposure to AA may have impacts on the molecular pathways of aging and related diseases by influencing α-klotho concentrations.